10 Finnish business actors' perceptions of their Chinese business partners and key personnel - Fay, Lisa Kaarina (2012)
The market impacts caused by globalization and the internationalization of companies are requiring the ability to operate in demanding, diverse and changing business environments but also requiring the consideration of differing cultural norms.